Challenges in Teaching: Perceptions and Experiences of Teachers of Ethics in Poland - Madalińska-Michalak, Joanna (Labor et Educatio, 2018)
This paper reports on a nationwide mixed methods study that investigated the challenges faced by teachers who teach ethics at schools in Poland. Several challenges affecting teachers in Poland were identified. These challenges included: qualifications of teachers; teacher education; didactics (teaching and learning); teaching materials and teaching aids; attractiveness of ethics as the subject at school; organization of work for delivering lessons of ethics; pupil traits and teaching programs; stereotypes related to the perception of ethics as the school subject. In the paper the special attention is paid to the challenges related to qualifications of teachers of ethics and their teacher education. The findings suggest that support provided for teachers of ethics must be aligned to local and school educational policies and educational conditions as well as strategies at national level. This paper contributes to understanding the complexities of the work of teachers who teach ethics at schools in Poland.